Estimation of serum glutamic oxaloacetic transaminase, serum glutamic-pyruvic transaminase, gamma-glutamyl transferase and cholesterol levels in prolonged (30 years) daily consumption coffee in people - Rani, J. Sudha; Raju, D. S. S. K. (International Journal of Research in Medical Sciences, 2016)
Background: Although prolonged (30years) coffee consumption has been associated with reduced or increased frequency of liver (SGOT, SGPT, GGT) enzymes and cholesterol levels, it is unclear whether the effect is from coffee or caffeine. Methods: A self-administered questionnaire ascertained lifestyle characteristics, including alcohol consumption, cigarette smoking, Diabetes mellitus and Dietary habits. As for drinking habit, examinees were first asked about their current drinking frequency (none, 1-2 times/ week, or almost daily) past or current smokers about the number of cigarettes smoked per day and the duration of smoking in years. As regards coffee, examinees were asked their usual daily intake in cups. Results: A total No of 200 cases were studied by dividing them into two group’s controls and cases. The results so obtain were compared with 50 healthy controls (not to consumed caffeine contained things that include nor coffee, tea, any type of cola’s). Statistical evaluation was carried out to confirm any deviation from the normal values. In men the mean serum SGOT, SGPT, GGT and cholesterol of cases is having higher level as compared to the mean value of controls. This increase is statistically highly significant (SGOT<0.0001, SGPT=0.045, GGT=0.0043, cholesterol<0.0001). In women’s the mean serum SGOT, SGPT, GGT and cholesterol of Cases is having higher level as compared to the mean value of Controls. This increase is statistically significant (SGOT< 0.05, SGPT=0.0319, GGT <0.0001, cholesterol: <0.0001). Conclusion: It has been shown from this study that prolonged daily consumption of coffee in many people it results increasing of levels of serum concentrations of the SGOT, SGPT, GGT and Cholesterol. It is observed that liver enzymes and cholesterol could be a target for caffeine or other components of coffee.